Exploring the Drivers of Poverty: A Comprehensive Review of Influential Factors - Ni Nengah Yuni Widya Pratiwi; Bala Ram Acharya; Abdulbasit Kolapo Imam; Tamara Franchuk; Ngwang Ngoongeh Norbert; Ranj Tahir Abdullah; Mugaahed Saleh (Indonesian Development Economics and Localities, 2025)
Poverty remains a complex and profound issue impacting both individual well-being and national economic development. In Indonesia, despite numerous initiatives by the government, academia, and non-governmental organizations, poverty persists at significant levels. This literature review aims to provide a comprehensive analysis of the factors influencing poverty rates in Indonesia. Key factors identified include population growth, education, and minimum wages. Population growth can exacerbate poverty if not matched by economic and social support. Education plays a crucial role in enhancing skills and employment opportunities, thereby alleviating poverty. Minimum wages are also pivotal in ensuring that workers can meet their basic needs. This review synthesizes findings from various studies to offer insights into how these factors interact and influence poverty levels. A thorough understanding of these dynamics is essential for developing more effective and sustainable poverty alleviation strategies. The methodology employed is a literature review, which systematically evaluates existing research to identify patterns, gaps, and potential solutions for addressing poverty in Indonesia.